Effect of heat treatments on superconducting properties and connectivity in K-doped BaFe2As2 - Chiara Tarantini (Nature Portfolio, 2021)
Abstract Fe-based superconductors and in particular K-doped BaFe2As2 (K-Ba122) are materials of interest for possible future high-field applications. However the critical current density (J c ) in polycrystalline Ba122 is still quite low and connectivity issues are suspected to be responsible. In this work we investigated the properties of high-purity, carefully processed, K-Ba122 samples synthesized with two separate heat treatments at various temperatures between 600 and 825 °C. We performed specific heat characterization and T c -distribution analysis up to 16 T and we compared them with magnetic T c and J c characterizations, and transmission-electron-microscopy (TEM) microstructures. We found no direct correlation between the magnetic T c and J c , whereas the specific heat T c -distributions did provide valuable insights. In fact the best J c -performing sample, heat treated first at 750 °C and then at 600 °C, has the peak of the T c -distributions at the highest temperatures and the least field sensitivity, thus maximizing H c2 . We also observed that the magnetic T c onset was always significantly lower than the specific heat T c : although we partially ascribe the lower magnetization T c to the small grain size (< λ, the penetration depth) of the K-Ba122 phase, this behaviour also implies the presence of some grain-boundary barriers to current flow. Comparing the T c -distribution with J c , our systematic synthesis study reveals that increasing the first heat treatment above 750 °C or the second one above 600 °C significantly compromises the connectivity and suppresses the vortex pinning properties. We conclude that high-purity precursors and clean processing are not yet enough to overcome all J c limitations. However, our study suggests that a higher temperature T c -distribution, a larger H c2 and a better connectivity could be achieved by lowering the second heat treatment temperature below 600 °C thus enhancing, as a consequence, J c .